Kreativitas Guru Dalam Meningkatkan Hasil Belajar Siswa Pada Pembelajaran PAI Kelas IV Di Sekolah Luar Biasa Negeri Lubuklinggau - Nuraliyah, Nuraliyah; Komalasari, Bakti; Indrawari, Karliana (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
Creativity is an ability to generate new ideas that are useful in solving problems or challenges faced in everyday life. Learning Islamic religious education is learning that is done by connecting several subjects related to everyday life. Learning outcomes are changes in behavior as a result of the educational process in accordance with educational goals. The aims of this study were to: (1) determine teacher creativity which can improve student learning outcomes in Islamic Religious Education class IV Lubuklinggau State Special School, (2) determine student learning outcomes in Islamic Religious Education learning class IV Lubuklinggau State Special Special School. To achieve some of the above objectives, researchers used field research with a qualitative descriptive approach and data sources were primary data and secondary data. Data collection techniques include observation, interviews and documentation. The results of the study show that, (1) teacher creativity that can improve student learning outcomes in Islamic Religious Education learning includes: in opening lessons in class doing ice breaking, presenting learning using learning media, appreciating student work by displaying it in class, and when closing learning motivate students. (2) Student learning outcomes in Islamic Religious Education class IV Lubuklinggau State Special School, previously the average student daily test score was 77,38 and now has increased the student's average daily test score to 80,3.